2009
DOI: 10.1179/174328109x445732
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of dual purging location for better mixing in ladle: a water model study

Abstract: Mixing time studies were performed on a one-fifth scale aqueous model of a single tapered ladle with different bottom purging locations. Two porous plugs were used simultaneously to purge compressed air as an analogue to argon and this was referred as dual purging. KCl solution (1 N) was used as the tracer for measuring mixing time. The scaled down gas flowrate varied from 10 to 80 L m 21 . Around 400 experiments were done including all possible dual purging locations and the location which gives least mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Although efforts have been made to optimize the operation of the ladle, in most cases only the minimization of mixing time is considered and the optimization is not performed using formal algorithms [16][17][18][19]. Recently, Mazumdar et al [11] and Jardón-Pérez et al [20] performed optimizations of mixing time and slag eye area in physical models of a ladle using formal algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Although efforts have been made to optimize the operation of the ladle, in most cases only the minimization of mixing time is considered and the optimization is not performed using formal algorithms [16][17][18][19]. Recently, Mazumdar et al [11] and Jardón-Pérez et al [20] performed optimizations of mixing time and slag eye area in physical models of a ladle using formal algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous investigations involving mixing phenomena indicate that mixing time increases due to the presence of the top slag layer. (Kim and Fruehan, 1987;Joo and Guthrie, 1992;Zhu et al, 1995;Jauhiainen et al, 2001;Chiapparoli et al, 2003;Chen et al, 2007;Chattopadhyay et al, 2009;Geng, et al, 2010;Liu et al, 2011;Lou and Zhu, 2014;Patil et al, 2010;Haida et al, 1983;Ying et al, 1983;Yamashita et al, 2003;Mazumdar and Kumar, 2004). The explanation is due to energy consumed to stir the slag and formation of the spout.…”
Section: Effect Of Separation Angle Nozzle Radial Position and Top Smentioning
confidence: 99%
“…The benefits of this configuration compared with the original design (90 degrees and asymmetric position at 0.67R and 0.79R) reported shorter mixing times in the water model and slightly better desulfurization rates in plant trials. Chattopadhyay et al (2009) included symmetric and asymmetric nozzle positions and three separation angles. In general, the shortest mixing time was achieved with a separation angle of 135 degrees and the two nozzles placed asymmetrically, 0.75R and 0.25R, however, at high gas flow rates the symmetric position at 0.5R and a separation angle of 180ºC reported not only a shorter mixing time but also less erosion of the refractory.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that eccentric bottom blowing is in favor of bath mixing in the ladle [7,10]. Some investigators also found that the position of porous plugs, gas flow rate and the size of ladle have an abundant influence on bath mixing in the ladle [4,5,[11][12][13][14][15][16][17]. It was discovered that the top slag layer could consume some part of kinetic energy of flow and enlarge the mixing time of the ladle [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%